Verified: Self-presentation, identity management, and selfhood in the age of big data. (3rd April 2017) - Hearn, Alison
ABSTRACT: What new styles of selfhood and self-presentation, forms of social status, and arbiters of "authenticity" are being authorized and propagated in the wake of big data and affective capitalism? How are they functioning, for whom, and to what end? This article takes up these questions via an examination of a sought-after user identity badge, the Twitter verification checkmark, figuring it as both an affective lure that incentivizes specific styles of self-presentation and a disciplinary means through which capitalist logics work to condition and subsume the significance of the millions of forms of self-presentation generated daily. Beneath the promise of democratized access to social status and fame, the business practices of the social platforms in and through which we self-present draw us into privatized strategies of social sorting, identity management, and control. To conclude, the article will posit a new "ideal type" of selfhood for the big data age.